Caracterización del Sistema de Tenencia, Morfometría, Perfil Hematológico y Bioquímico del Ovino Criollo Ecuatoriano en la Provincia de Cotopaxi - Abata Mesias, Cynthia Gissela (2019)
This research project was carried out in the province of Cotopaxi, in the rural parishes of Pujilí Town. Due to the lack of information of the Creole sheep it is opportune to create documents with the aim of characterize the system of ownership, morphometry, hematological and biochemical profile of the Creole sheep as a contribution for the conservation of this species. For the ownership study, surveys were applied to the owners of the herds, thus 7 parameters were evaluated which encompass general, reproductive, productive, health, food and human data; for morphometry, measurements were taken one hundred adult sheep analyzing 15 body regions divided into measurements cephalic, extremities, trunk and rump while hematology and biochemistry blood samples are taken from sixty sheep greater than one year considering young sheep (<two years) and adults (> two years old), in which 7 hematological variables, 6 white series variables and 6 biochemical variables are analyzed, using manual and automated techniques for analysis. The obtained results were assessed using descriptive statistics, numerical values were analyzed in the InfoStat program, obtaining values such as average, standard error and maximum and minimum values, when evaluating the sex and age factor for morphometry, hematologic and biochemical profile the data was submitted to the statistical study ANOVA. The obtained results were evaluated using descriptive statistics and numerical values were analyzed in the InfoStat program, obtaining values such as the mean, the standard error and maximum and minimum values, When evaluating the sex factor for morphometry and the age and sex factor in the hematological and biochemical profile, the data is subjected to the ANOVA statistical study. Characterizing that creole sheep are developed with rustic techniques, they do not have health calendars and reproductive protocols are not used, their diet does not have the necessary requirements for sheep as productive animals, Creole sheep are animals with reduced morphometry compared to other breeds, the layer is white, have a straight cephalic profile, the ears are horizontal and present dark pigmentation of mucous and hooves, regarding the Hematological and Biochemical parameters, the same ones are within the ranges of normality in comparison with the Creole sheep Lanada Serrana. When analyzing the sex factor in morphometry, Significance level was obtained in the width and length of the rump of the females, for studying the same factor, a level of significance is seen in the white series and biochemical profile, on the other hand, both profiles are affected by the age factor since variables such as hematocrit, neutrophils, creatinine and calcium have a high level of significance. In conclusion, the sex factor affects the white series and the biochemical profile, whereas the age factor directly influences both profiles of Creole sheep, being the environmental, sanitary conditions and situations like the stress that the sheep go through, the possible reasons why they would have certain parameters with variability.